Idealistic incentives in non-governmental organization innovativeness: bridging theoretical gaps. (1st June 2017) - Lindberg, Malin; Nahnfeldt, Cecilia
Abstract : This paper bridges the theoretical gap between traditional innovation studies and more recent studies of innovation among civil society actors and contexts. The paper presents a study of the nature and function of idealistic incentives in innovativeness of non-governmental organizations (NGOs) based on case studies of two national NGOs in Sweden, the Sensus Study Association and the Church of Sweden. The results show that the idealistic incentives of a basic view of human beings focusing on dignity and solidarity in the studied cases are closely related to various forms of NGO innovativeness, including the identification of challenges and needs, the aspired change at individual, organizational and societal levels, the involvement of concerned groups, and in cross-organizational and cross-sectoral cooperation. This contributes new knowledge not only of what NGO innovation entails and how it is brought about, but also of why such processes are initiated and thus why individual, organizational and societal transformation is essential in such processes. As part of this, the probable impact of beliefs, norms, ideologies and identities on all innovation processes, regardless of sectoral context, is highlighted.